2022
DOI: 10.1021/acsapm.2c01702
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkylsilane-Modified Boron Nitride Nanosheets for Epoxy Composites with Improved Thermal Conductivity and Dielectric Performance

Abstract: The development of polymer-based packaging materials with excellent heat dissipation capacities and low dielectric constants is increasingly desired for the modern microelectronic industry. Herein, boron nitride nanosheets (BNNSs) were coated with polydopamine (PDA) and subsequently grafted with tridecafluorooctyl trimethoxy silane. Compared with unmodified BNNSs, as-prepared perfluoroalkylsilane-modified BNNSs (PFOS-BNNSs) show distinctly improved miscibility in the epoxy matrix. Consequently, the epoxy/PFOS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…Figure 4D summarizes the thermal conductivity of polymer composites with BN as a thermally conductive filler reported in recent years and compares it with this paper. [37][38][39][40][41][42][43][44][45] The thermal conductivity of the sample prepared in this paper is significantly better than that reported in other papers under the condition of the same filler load. For composites obtained by physical blending, BN particles are randomly dispersed within the resin matrix, which leads to severe phonon scattering at the "organicinorganic" interface.…”
Section: Thermal Conductivity Of Compositescontrasting
confidence: 54%
See 1 more Smart Citation
“…Figure 4D summarizes the thermal conductivity of polymer composites with BN as a thermally conductive filler reported in recent years and compares it with this paper. [37][38][39][40][41][42][43][44][45] The thermal conductivity of the sample prepared in this paper is significantly better than that reported in other papers under the condition of the same filler load. For composites obtained by physical blending, BN particles are randomly dispersed within the resin matrix, which leads to severe phonon scattering at the "organicinorganic" interface.…”
Section: Thermal Conductivity Of Compositescontrasting
confidence: 54%
“…This structure with dual heat transfer channels enables efficient heat transmission. Figure 4D summarizes the thermal conductivity of polymer composites with BN as a thermally conductive filler reported in recent years and compares it with this paper 37–45 . The thermal conductivity of the sample prepared in this paper is significantly better than that reported in other papers under the condition of the same filler load.…”
Section: Resultsmentioning
confidence: 54%
“…All these temperatures are above 200°C, indicating that SRVs exhibit high heat resistance. The heat resistance index ( T HRI ) [ 46 ] of the SRVs are determined to be 138.6, 148.6, 139.8, and 138.2 °C, respectively, demonstrating a trend of initially increasing and then decreasing. When R is 0.8, the SRV shows the highest T HRI of 148.6 °C.…”
Section: Resultsmentioning
confidence: 99%
“…So, the single h-BN-filled geometric model seems inappropriate for studying the synergistic impact on the overall thermal conductivity . Additionally, some studies have indicated that the effective thermal conductivity of composites closely correlates to the properties of interface because the generated interface thermal resistance affects heat transfer, but the interface components are usually absent for many built finite element models. Therefore, the randomly generated geometric model needs to be further developed, and a comprehensive analysis of the role of the variable is highly desired.…”
Section: Introductionmentioning
confidence: 99%